Quatro Canções de Edino Krieger: um Estudo Analítico - Ramos, Helenilce Eleutério de Paula (2018)
The main objective of this research is to understand the compositional procedures of Edino Krieger through the analysis of four songs for voice and piano, chosen according to his three compositional phases: Tem Piedade de Mim (1946), lyrics by Antônio Rangel Bandeira, Desafio (1955), poem by Manuel Bandeira, Canção do Violeiro (1956), verses by Castro Alves and Silêncios (2003), text by Cruz and Souza. A historical contextualization was carried out relating these songs with the three different stylistic periods lived by the composer, pointing out to the transformation of his creations as he matured his ideas and musical language. The analytical process used for understanding the compositional procedures comprises: 1º) an analysis of the poetic text approaching the rhythmic and sonic aspects, the lexical, syntactic and semantic analysis of the poem; 2º) an analysis of the musical structure in order to understand the melodic, harmonic, rhythmic, formal e textual aspects and the text-music relations. After studying the literary aspects of the poem and the analysis of the musical structure, a comparative approach was made between the songs and the three phases of Edino Krieger's musical production, presenting the main differences between them, as well as identifying the common link that permeates all his compositional phases.